Balancing Performance Measurement By Using The Tradition Of Islam, Tao, And Java - Triyuwono, Iwan (Accounting Department,, 2007)
Traditional financial measurement (e.g. return on investment) is usually utilized to measure management performance. However, it does not adequately represent the real performance of management. An alternative is offered, i.e. â€œBalanced Scorecardâ€ (BS).Â It is not only treated as a performance measurement, but also as strategic management systems.Â BS is more extensive and equitable than the traditional one. This paper evaluates and examines the gender of traditional financial measurement (ROI) and BS through a cultural analysis, i.e. Islam, Tao and Javanese tradition.Â Having evaluating the gender of the measurements, the paper continually evaluates their weaknesses and attempts to reformulate them in a proper manner.Â An instrument of analysis is formulated based on Islam, Tao and Javanese tradition.Â In essence, the instrument utilizes â€œsynergy of binary oppositionâ€ which deconstructs â€œthe Centerâ€ through internalizing â€œthe others.â€ The results of the analysis indicate that the performance measurements are strongly masculine-laden.Â The masculine values are the ones that tend to be expansive and destructive for social orders of human life and natural environment.Â To eliminate the negative effects of the masculine values, the paper suggests modification of the performance measurements by harmonizing and balancing masculine values with feminine ones. Key words: return on investment, balanced scorecard, deconstruction, binary opposition, Islam, Tao, Javanese tradition, Masculine and feminine values